PT VKP's competitive strategy architecture in the healthcare digitalization industry - Hutama, Dwinanda; Indrawan, Raden Dikky; Hannan, Sufrin (International Journal Labs, 2024)
Indonesia's digital transformation has led to the emergence of startups like PT VKP, which focuses on the healthcare service segment. The company aims to optimize business opportunities in this segment, but the lack of mass vaccinations after Covid-19 has impacted the number of active consumers. To remain competitive, PT VKP must develop a strategic architecture strategy. The study analyzed the company's internal and external factors, conducted a competitive advantage analysis, and formulated a competing strategy architecture. Externally, the digital health industry presents an opportunity, while competitors' product diversification poses a threat. Internally, the company's ability to build relationships with partners is its strength, while its weakness is limited product features. Six alternative competitive strategies were identified, with the main focus being on making sales in the health service category. PT VKP will implement these strategies in four phases over a year.